Kazakhstan Legislation for Allocation of Mining Exploration Rights : Report 1. Allocation of Exploration Rights for Mining in a Sample of Major Global Mining Countries - World Bank (Washington, DC, 2014)
This study has been undertaken to provide input to the Government of Kazakhstan on mineral exploration policy. The purpose is to offer advice for policy reform in the mineral sector. It examines best practices in licencing and regulation for mineral exploration. It will review common best practices which pertain to mineral exploration on a world-wide basis. It will also provide examples of countries which have instituted best practices in their legislation and how that has assisted in attracting foreign investment in the sector. Countries which will be studied are Australia (Western Australia), Chile, Sweden, Ghana and the Philippines. Other countries are discussed to provide a necessary example of the need for transparency, consistency and fairness. These are Argentina and Mongolia. Information on each of these countries is different depending upon the transparency of information that is available. This study has attempted to show how these countries have dealt with international investment through policy and legislative initiatives.